Cohetes hidráulicos diseño, construcción y experimentación una experiencia integradora - Acosta Vásquez, Edgar Alejandro; Marín, Luis Eduardo; Jaimes, Oscar (Revista Científica, 2011)
This task shows the experience that students at Fundacion Educativa de Montelibano have had with their projects designing hydraulic rockets. The objective is to gain meaningful experiences while learning in a funny environment. For our school, knowledge means, besides understanding scientific and technological aspects, grasping cultural and social backgrounds related to natural facts that leads to integrate learning systems.